The Prevalence and the significance of the Pulmonary Bacterial Super-Infections among Hospitalized COVID-19 patients : A scoping Review - Musa, Muslim (University of Thi-Qar Journal of Science, 2023)
Mortality of any respiratory viral diseases usually attributed in part to other reasonse than damaging effect of the virus alone. One of these reasons is the bacterial superinfection. For this reason, this scoping review attamt to evaluate the significant conterbution of bacterial super-infection on the mortality among hospitalized COVID-19 patients and also to determine the true revalence of bacterial super-infections in that population. Accordingly, a systematic search was employed with precise criteria on the MEDLINE, SCOPUS, PUBMED, and GOOGLE SCHOLAR databases published in the English language in the period of three years from January 2020 to January 2023. The Prevalence of bacterial super-infection (BSI) among COVID-19 patients constitutes a point of contention among publications. this heterogeneity among publications came from the semantic dilemma of co-infection and super-infection. co-infection was determined to be found in a relatively narrow range (1.2-3.1%) while, Prevalence of bacterial super-infection among COVID-19 patients varied from 18.2 to 50%. The bacterial super-infection appears to significantly increase COVID-19 mortality, with the Odd ratio ranging from 1.76 to 10.53 [CI 95%]. Bacterial super-infection among hospitalized COVID-19 patients represents a non-recognized threat, especially during the first wave of the pandemic. The Prevalence of bacterial super-infection is comparable with those observed in previous influenza and SARS epidemics. A significant contribution of bacterial super-infection, especially the pulmonary to mortality of COVID-19 patients, was observed clearly